The Strategic Role of ICT in Islamic Higher Education - Dody Yogaswara (Edumaspul: Jurnal Pendidikan, 2023)
Times continue to change, cultural shifts continue to occur continuously. The world of education is no exception. It is inevitable that the erosion of information and communication technology will continue to touch the world of education. From management, learning and finances, the use of information and communication technology can be maximized.This research method is a qualitative research method with a case study approach. A case study is a model that focuses on "bounded system" exploration of one case or several cases in detail by extracting data in depth. Various sources of information that are rich in context are used for data mining.. Basic Concepts of Information and Communication Technology, The Role of ICT in the Learning Process in Higher Education and Supporting Institutional Administration, Stai Nurul Ilmi Tanjungbalai slowly began to complete the infrastructure for managing the campus and conducting learning. The room is provided with multimedia equipment and WiFi which can be used as a source of learning material.In the end, based on the experience of universities that have successfully used ICT to improve performance, it can be said that the ICT "invasion" in the world of higher education will not be successful. Campus human resources must be ready to change their paradigm, way of thinking and daily habits.